STUDENTS’S PERCEPTIONS IN USING GRAMMARLY AND QUILLBOT FOR IMPROVE WRITING SKIIL AT MA ANNUR TELUK PALINGET GRADUATE STUDENTS OF PALANGKARAYA UNIVERSITY - Bahing; Mayang Meilantina; Wahipal Akhmad; Bahing Bahing (Bajang Institute, 2025)
By using a descriptive quantitative design, data were collected through a cross-sectional survey. The population included 95 students from grades 10 to 12 who regularly used both tools for English writing. After a pilot test with 30 students, 65 students were selected as the final sample. Data were gathered using a validated questionnaire via Google Forms, covering four dimensions: tool features, Grammarly and QuillBot are al-power tool that help users identity and correct grammar, vocabulary, and sentence structure errors. All these tools become more common in Education, understanding students’ perception of their effectiveness is essential for optimizing their use in EFL writing instruction. This research explores students’ perceptions of Grammarly and quillBot for writing development at Ma Annur Teluk Palinget in the year of 2025 by focusing on Grammar improvement and the factors shaping those perception.feedback quality, knowledge and ability development, and learning experience. Analysis used frequency, percentage, and mean scores in Microsoft Excel. Validity (Pearson > 0.349) and reliability (Cronbach's Alpha = 0.967) were confirmed through pilot testing. The results indicate that students at MA Annur Teluk Palinget held very positive perceptions of both Grammarly and QuillBot, with identical overall mean scores of 3.85. All dimensions—features, feedback quality, knowledge development, and learning experience—were rated very positively, with over 80% strongly agreeing that the tools provided helpful grammar feedback, clear suggestions, and useful explanations. Students particularly noted improvements in understanding subject-verb agreement (89%), sentence structure (85%), and tense consistency (80%), along with increased confidence and motivation. These perceptions were primarily shaped by three factors: accessibility (mean: 3.91), educational effectiveness (3.84), and user experience (3.83), which explained 77% of the total variance. While a small number of students raised concerns—such as language barriers, internet dependence, and feedback accuracy for complex grammar—both tools significantly supported grammar improvement and were seen as suitable for integration into high school EFL instruction